Os caminhos de João da Maia da Gama: práticas governativas, guerra e comércio na administração da capitania da Paraíba (1708-1717) (Ágora Journal, 2021)
The captain-major and governor João da Maia da Gama commanded the captaincy of Paraiba over nine years (1708-1717). During his term, João da Maia took part actively in the colonial administration, outlining plans and strategies in the political, economical and military areas, including an involvement in the Guerra dos Mascates (1710-1711) in Pernambuco. The present article intends to observe his governance practices, scrutinize his involvement in commercial activities, analyse the attempts at enlarging his own jurisdiction, the jurisdictional disputes with other colonial authorities and his intervention in Pernambuco’s conflict. The episodes presented in this article highlight the governor´s role in the exercise of his governmental functions, in the midst of attitudes that are not always in accordance with royal instructions.